Strategi Pengembangan Agroindustri Kopi di Kabupaten Kerinci - Dina Yuliasty Lamefa; Sukardi Sukardi; Sapta Raharja (Jurnal Agro Industri Perkebunan, 2020)
Coffee is one of the plantation products with significant importance in the economy of Kerinci Regency, and several obstacles have been reported in agroindustry development. This study is focused on designing a strategy to develop the industry in the region. The study was conducted in Kerinci Regency from January 2017 until October 2017. The data was collected by observation, questionnaires, and in-depth interviews through Focus Group Discussion (FGD). In addition, research analysis used internal and external factor methods, internal and external matrices (IE Matrix), and SWOT matrices. The result show the value of the internal and external factors obtained to be 2,759 and 2,888, respectively. When mapped, the IE matrix value is in cell V (five). However, the suitable strategies are the growth and stability strategy, essential for market penetration and product development. Based on AHP analysis, the three main strategic priorities to be applied  are land expansion (0,230), guidance and facilitation of the market information (0,178), and infrastructure improvement (0,124)